Technical report: mathematical modelling of brain tumour growth / Amalina Rafli - Rafli, Amalina (2017)
Tumour is a disease that has been a biological study since 60 years ago. A lot of tumour growth curves have been developed and most of the successful models are as an extension of the classical Verhulst equation. This project is done to describe and compare two of those models, which are Logistic and Gompertz. The comparison is then made to see the best model in modelling tumour growth. In this project, such models are reviewed, solved and investigated their interests of properties. Besides, a report on limitations and assumptions of the models are also made. In order to see the behaviour of the models, a few curves are constructed to see the similarities and differences. As results, Gompertz model has given a better accuracy in modeling tumour growth due to its realistic properties, compare to the Logistic model.